Climate Change, Disasters and People on the Move Providing Protection under International Law - Noorda, Aylin Yildiz (Brill, 2022)
Climate change is forcing us to consider the right of people to leave their disappearing homelands, and the shape this right should take. Climate Change, Disasters and People on the Move proposes international protection as a solution with three pillars: granting protection against return to the country of origin (non-refoulement); preventing future displacement; and facilitating safe, orderly, and regular migration in the context of disasters and climate change. Dr. Aylin Yildiz Noorda uses the theories of common concern of humankind and community interests to operationalise her proposal, providing a blueprint for future claims.